The Role of Signal Transducer and Activator of Transcription 3 (STAT3) in Tumor Immunity - Oeij Anindita Adhika; M Nurhalim Shahib (The Prodia Education and Research Institute (PERI), 2012)
BACKGROUND: Inflammation is a key component of the tumor microenvironment. Cancer-associated inflammation is marked by the presence of specific inflammatory cells and inflammatory mediators. Moreover, immune cells in the tumor microenvironment not only fail to mount an effective antitumor immune response, but also interact intimately with the tumor cells to actively promote oncogenesis.CONTENT: Their roles in regulating cytokine-dependent inflammation and immunity make the signal transducer and activator of transcription (STAT) proteins critical players in determining whether immune responses in tumor microenvironment promote or inhibit cancer. Recent evidence suggests a crucial role for STAT family proteins, especially STAT3 (signal transducer and activator of transcription 3), which is a point of convergence for numerous oncogenic signaling pathways, in selectively inducing and maintaining a procarcinogenic inflammatory microenvironment, both at the initiation of malignant transformation and during cancer progression. The persistent activation of STAT3 increases tumor cell proliferation, survival, and invasion while supressing antitumor immunity. SUMMARY: STAT3 signaling pathway constitutes a potential preventive and therapeutic target for cancer immunotherapy. KEYWORDS: STAT3, inflammation, tumor microenvironment, cancer immunotherapy